Cellular Heterogeneity and Cooperativity in Glioma Persister Cells Under Temozolomide Treatment - Rabé, Marion; Fonteneau, Lucie; Oliver, Lisa; Morales-Molina, Alvaro; Jubelin, Camille; Garcia-Castro, Javier; Heymann, Dominique; Gratas, Catherine; Vallette, François M. (Frontiers in Cell and Developmental Biology, 2022)
We have observed a drug tolerant/persister state in a human glioblastoma (GBM) cell line after exposure to Temozolomide (TMZ), the standard-of-care chemotherapeutic agent for GBM. We used a multicolor lentiviral genetic barcode labeling to follow cell populations evolution during TMZ treatment. We observed no change in the distribution of the different colored populations of cells in persister or resistant cells suggesting that pre-existing minor subpopulations, which would be expected to be restricted to a single color, were not amplified/selected during the response to the drug. We have previously identified 4 genes (CHI3L1, FAT2, KLK5 and HB-EGF) that were over-expressed during the persister stage. Single cell analysis of these 4 genes indicated that they were expressed in different individual cells ruling out the existence of a single persister specific clone but suggesting rather a global answer. Even so, the transitory silencing of CHI3L1, FAT2 or KLK5 influenced the expression of the other 3 genes and the survival of U251 cells in absence of TMZ. Since proteins encoded by the 4 genes are all localized in the extracellular matrix or interact within the extracellular compartment, we propose that cellular interactions and communications are important during the persister stage. Thus, the cellular co-operation implicated in the drug tolerance/persister stage before the acquisition of chemo-resistance could be a new therapeutically relevant target.